Using Metacognitive Strategies in Second Language Learning: A Bibliometric Analysis - Prihatini, Arti; Pangesti, Fida; Zamahsari, Gamal Kusuma (Linguists : Journal of Linguistics and Language Teaching, 2024)
Metacognitive strategies can help students learn autonomously, so they have been studied in second language learning. However, mapping research trends and future challenges on this issue is rare. This study aims to conduct a bibliometric study using metacognitive strategies in second language learning. Scopus papers from the past decade provide data. Descriptive statistics and Vosviewer were used to analyse data. The results showed six research clusters: (1) the use of metacognitive strategies in achieving learning outcomes, (2) students’ motivation and awareness in a second language, (3) teaching writing, (4) learning interventions and their effects on students’ comprehension and abilities, (5) learning activities, problems, and reflections in learning a second language, and (6) courses related to learning a second language. Cluster 6 has the weakest relationship with other clusters in their study. Year-to-year research themes developed. Research focuses on managing course programs in the early five years by utilising metacognitive strategies, technology, motivation, and student awareness. From mid-2018 to 2019, research trends have developed in learning to write. After that, there are no new research trends to date. Trends address second language learning outcomes, student motivation and self-awareness, learning interventions, and their effects. Student issues research themes are rarer.